2003
DOI: 10.3727/000000003108747226
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Insulin Secretion from Encapsulated Islets

Abstract: Adequate regulation of glucose levels by a microencapsulated pancreatic islet graft requires a minute-tominute regulation of blood glucose. To design such a transplant, it is mandatory to have sufficient insight in factors influencing the kinetics of insulin secretion by encapsulated islets. The present study investigates factors influencing the glucose-induced insulin response of encapsulated islets in vitro. We applied static incubations and did the following observations. (i) Small islets (90-120 µm) showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 31 publications
2
47
0
Order By: Relevance
“…First it has been found, repeatedly, not to interfere with cellular function of the islets [24][25][26]. Alginate is one of the few materials that allows for processing of the capsules at physiological conditions.…”
Section: Article In Pressmentioning
confidence: 99%
“…First it has been found, repeatedly, not to interfere with cellular function of the islets [24][25][26]. Alginate is one of the few materials that allows for processing of the capsules at physiological conditions.…”
Section: Article In Pressmentioning
confidence: 99%
“…The study by Chicheportiche and Reach was the first to investigate the effects of alginate encapsulation on insulin release and concluded that small beads (300 lm in diameter) released more insulin than larger beads (800 lm diameter) (Chicheportiche and Reach 1988). A more recent study by de Haan et al concluded that it was the porosity of the alginate/ poly-L-lysine (PLL) matrix, i.e., the time that alginate was allowed to interact with PLL, that was critical to insulin release, while capsule diameter (for capsules up to 800 lm in diameter) did not affect insulin release (de Haan et al 2003). Although these and other reports (Fritschy et al 1991;van Schilfgaarde and de Vos 1999;Lembert et al 2001;Rasmussen et al 2003) describe the effects of alginate encapsulation on the quantity of insulin released over a period of time, they do not detail the effects of encapsulation on the precise dynamics of insulin secretion in response to physiologic stimuli.…”
Section: Introductionmentioning
confidence: 97%
“…Microencapsulation provides a semipermeable membrane that prevents the passage of antibodies but allows for passage of cell-derived therapeutic factors ( 2 ). Despite this semipermeability, encapsulation methods are often hindered by their inability to provide suffi cient oxygen for long-term graft survival ( 3 ). Studies have shown that while nonencapsulated islets are completely vascularized after transplantation ( 4 ), encapsulation prevents the neovascularization process and thus fresh fl ow of oxygen, which can eventually lead to graft necrosis ( 5 ).…”
Section: Methodsmentioning
confidence: 99%